2013
DOI: 10.1590/1516-3180.2013.1313479
|View full text |Cite
|
Sign up to set email alerts
|

Accidents due to falls from roof slabs

Abstract: CONTEXT AND OBJECTIVE: Falls from the roof slabs of houses are accidents of high potential severity that occur in large Brazilian cities and often affect children and adolescents. The aims of this study were to characterize the factors that predispose towards this type of fall involving children and adolescents, quantify the severity of associated lesions and suggest preventive measures. DESIGN AND SETTING: Descriptive observational prospective longitudinal study in two hospitals in the metropolitan region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…reported that the prevalence of non-fatal injuries in 5-9-year-old children was significantly higher (19.3 per 1000 subjects) than in 10-14 years old children (15.1 per 1000 subjects) [4]. In our study the most common site of injury is limb in children older than 6 years, and head injury is more common in toddlers those results are similar to a study in Texas where children had more injuries in limbs and younger children had head trauma [18,19].…”
Section: Discussionsupporting
confidence: 88%
“…reported that the prevalence of non-fatal injuries in 5-9-year-old children was significantly higher (19.3 per 1000 subjects) than in 10-14 years old children (15.1 per 1000 subjects) [4]. In our study the most common site of injury is limb in children older than 6 years, and head injury is more common in toddlers those results are similar to a study in Texas where children had more injuries in limbs and younger children had head trauma [18,19].…”
Section: Discussionsupporting
confidence: 88%
“…Neste contexto, percebe-se que a queda na infância é concebida como acontecimento normal do cotidiano infantil. Todavia, além de estarem intimamente relacionadas com a fase da infância, refletem falha na capacidade protetora da família e o desconhecimento de fatores de risco, o que pode ocasionar graves sequelas e problemas futuros, indicando a necessidade de intervenção para prevenção (20,21) . Ainda sobre a causa do trauma, percebeu-se na pesquisa em questão que o acidente de trabalho aparece como terceira causa, com maior incidência em indivíduos do sexo masculino e no grupo etário de 19 a 59 anos.…”
Section: Discussionunclassified
“…In 72% of the cases, the children were unaccompanied by an adult responsible for them, which calls attention to prevention measures as informing parents and physical protective measures as gates with lockers to restrict free access to these areas. 28 The aging process implies changes in reflexes and balance control, jeopardizing the body mobility as well as reduced speed and strength. In a recent systematic review, it was concluded that interventions to prevent falls in the elderly have been effective, with 10% reduction in rates of fall.…”
Section: Discussionmentioning
confidence: 99%